2021
DOI: 10.1007/s10643-021-01181-6
|View full text |Cite
|
Sign up to set email alerts
|

Making Partnerships Work: Proposing a Model to Support Parent-Practitioner Partnerships in the Early Years

Abstract: Building on Froebelian principles that highlight the importance of family and community, this study explored the importance of collaboration and communication as part of a two-way dialogue. The aim was to identify the key characteristics of a model that would encourage interest and commitment to partnerships from both parents and practitioners. The idea of such partnerships has a solid theoretical background and is supported both rhetorically and by legislation by the Department of Education. However, research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 38 publications
3
15
0
Order By: Relevance
“…Much of this is contained with the ‘communicating’ aspect of involvement ( Epstein, 2010 ), where parents asked for there to be more two-way or meaningful communication on food and nutrition, a finding that supports other studies ( Dev et al., 2017 ; Johnson et al., 2013 ; Kambouri et al., 2021 ; Luecking et al., 2020 ). Dipti and colleagues, in their study on engaging parents to promote nutrition and health in pre-school EYS, identified a range of barriers to communication, including parents being too busy to talk to providers, and providers unsure of how to communicate about nutrition without offending parents ( Dev et al., 2017 ).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Much of this is contained with the ‘communicating’ aspect of involvement ( Epstein, 2010 ), where parents asked for there to be more two-way or meaningful communication on food and nutrition, a finding that supports other studies ( Dev et al., 2017 ; Johnson et al., 2013 ; Kambouri et al., 2021 ; Luecking et al., 2020 ). Dipti and colleagues, in their study on engaging parents to promote nutrition and health in pre-school EYS, identified a range of barriers to communication, including parents being too busy to talk to providers, and providers unsure of how to communicate about nutrition without offending parents ( Dev et al., 2017 ).…”
Section: Discussionsupporting
confidence: 69%
“…Practitioner guidance on strategies to promote healthy eating are available in the UK, including ways to better involve and engage parents ( Action for Children 2017b ), and to support the development of parent practitioner partnerships in EYS ( Kambouri et al., 2021 ; PACEY ). Action for Children's ‘Eat Better, Start Better’ guidelines on food and drink in early years settings have ‘best practice around involving and engaging parents’, suggesting (a) all staff are able to share the EYS's approach to healthy eating with parents/carers and children; (b) families and children are consulted and encouraged to give feedback about the meals and snacks offered; (c) family and children's involvement in decision-making is included in the EYS self-evaluation’ and (d) families are encouraged to participate in food activities to support development of healthy cooking skills (Action for Children, 2017a , 2017b ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study done by Leite et al (2004) on community innovation and networking in Canada revealed that partnership by networking promotes the development of the organization through the enhancement of economic, social, political, and cultural capabilities; the creation, provision, and use of community-oriented learning opportunities; and the development of community-oriented cultural content, open source software, learning tools, and broadband infrastructures. These findings supported the Forebelian principles that highlight the importance of family and community, Postulated by Kambouri, (2022). The principle shows that partnership significantly contributed in enhancing community development.…”
Section: Regression Analysis To Determine the Relationship Between Ne...supporting
confidence: 78%
“…The theoretical frame of the study forms research about different programs to promote the cooperation between teachers and parents (Kapsalis et al, 2019), the partnership between teachers and parents (Jose, et al, 2020;Kambouri, et al, 2021), cooperation and collaboration between teachers and parents (Malik, 2021;Halpner, et al, 2021).…”
Section: Methodsmentioning
confidence: 99%